2018
DOI: 10.1007/s10943-018-0605-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Socialization and Religiosity in African American and Caribbean Black Adolescents’ Sexual Initiation

Abstract: This study determined the nature of the associations between religious socialization, religiosity, and adolescent sexual initiation. Data originated from the National Survey of American Life-Adolescent (n = 1170), a nationally representative study of black adolescents. Factor analysis, structural equation modeling, and logistic regression were used to evaluate hypotheses. Results indicated that as black adolescents received more messages about religious beliefs and practices, their religiosity was greater and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…For example, mentorship quality and the nature of support provided have been shown to augment the protective effect of natural mentoring relationships (Hurd, Albright, Wittrup, Negrete, & Billingsley, ; Hurd & Sellers, ; Wittrup et al., ). Third, although our study identified that high levels of ORI paired with natural mentorship was protective, religious socialization for some African American girls may shape the protectiveness of religious involvement (Bowie, Juon, Taggart, Thorpe, & Ensminger, ; Butler‐Barnes et al., ; Gutierrez, Goodwin, Kirkinis, & Mattis, ; Hope et al., Taggart et al, ). Thus, scholars should examine whether ORI may be particularly protective for Black youths who have received high levels of religious socialization from parents or other caregivers.…”
Section: Discussionmentioning
confidence: 83%
“…For example, mentorship quality and the nature of support provided have been shown to augment the protective effect of natural mentoring relationships (Hurd, Albright, Wittrup, Negrete, & Billingsley, ; Hurd & Sellers, ; Wittrup et al., ). Third, although our study identified that high levels of ORI paired with natural mentorship was protective, religious socialization for some African American girls may shape the protectiveness of religious involvement (Bowie, Juon, Taggart, Thorpe, & Ensminger, ; Butler‐Barnes et al., ; Gutierrez, Goodwin, Kirkinis, & Mattis, ; Hope et al., Taggart et al, ). Thus, scholars should examine whether ORI may be particularly protective for Black youths who have received high levels of religious socialization from parents or other caregivers.…”
Section: Discussionmentioning
confidence: 83%
“…In total, 21 studies met the inclusion criteria (see PRISMA diagram, Figure 1). Twelve study samples 23,25,[27][28][29][30]33,37,38,[41][42][43] included adolescents aged ≤17 years, five studies 24,26,34,35,39 included emerging adults aged 18-25 years, and four studies 31,32,36,40 included both adolescent girls and emerging adult women. Eighteen studies met 100% of the checklist criteria for inclusion in the review.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 most of the studies included in the review (n=14) were in metropolitan areas, and the remaining seven studies used nationally repre-sentative or regional samples. 24,31,[38][39][40][41][42] Seventeen studies used a cross-sectional study design and the remaining four studies used a longitudinal de- Life Course and HIV Risk in Black Women -Taggart et al sign. 26,27,29,32 Regarding study sample characteristics, one study focused on sexual minority adolescent girls, 33 one study focused on shelter-living homeless youth, 34 and three studies included parent-adolescent dyads.…”
Section: Resultsmentioning
confidence: 99%
“…The Likert response scale consisted of responses ranging from 1 ( very important ) to 4 ( not important ) or from 1 ( nearly every day ) to 6 ( never ). Exploratory and confirmatory factor analyses were used to assess and then test the factor structure of the index of religiosity used in this study (Taggart et al., ). We then generated factor scores for each dimension of religiosity.…”
Section: Methodsmentioning
confidence: 99%
“…Contradictory findings on the influence of religiosity on sexual initiation may be attributable to past studies operationalizing religiosity in a way that does not fully capture its multidimensionality or take into account other related factors that may intersect with religiosity to influence sexual initiation (Goggin, Malcarne, Murray, Metcalf, & Wallston, 2007;Taylor, Chatters, & Joe, 2011;Yonker, Schnabelrauch, & DeHaan, 2012). Although ethnic differences exist in the associations between religiosity and sexual health, some studies of Black adolescent religiosity and sexual health do not account for these differences (Ojikutu et al, 2013;Taggart et al, 2018). Additionally, much of the published adolescent religiosity and sexual health research uses samples that are disproportionately White and/or female (Yonker et al, 2012).…”
Section: Adolescent Religiosity and Healthmentioning
confidence: 99%